Long-term results of acetabular reconstruction using Ganz acetabular rings - Beckmann, Nicholas A.; Moradi, Babak; Schlegel, Ulf J.; Gotterbarm, Tobias; Streit, Marcus R. (The journal of arthroplasty, 2018)
Background - Our study examines the long-term results of acetabular reconstruction using the Ganz acetabular reinforcement ring (GRR) in total hip arthroplasty. - Methods - Between 1998 and 2001, 135 hips (119 revision and 16 primary arthroplasties) were consecutively implanted with a GRR at our hospital. The average age was 65 years (range, 26-90). Clinical and radiographic evaluations were carried out. Long-term survivorship was estimated using a competing risks analysis, and multivariate survivorship using Cox regression model was used to identify risk factors for implant failure. - Results - At a mean follow-up of 16 years (range, 15-18), 3 patients were lost to follow-up and 19 had implant failure: 4 aseptic loosenings without re-revision, 4 septic, and 11 aseptic re-revisions. Survival was estimated at 86% after 16 years (95% confidence interval [CI], 78.5%-90.9%) using radiographic loosening or revision for any reason as the end point. Using aseptic loosening as the end point, the survival was estimated at 91.2% after 16 years (95% CI, 84.5%-95.0%). Multivariate analysis revealed that age at surgery was a significant risk factor for failure of the GRR. With acetabular revision or loosening as the end point, patients ≤60 years had 71.6% (95% CI, 53%-82.8%) and older patients had 92.2% (95% CI, 84%-96.2%) probability of implant survival after a mean 16-year follow-up. The median Harris Hip Scores and Western Ontario and McMaster Universities Osteoarthritis Index scores were 77 and 64.5, respectively, and mean Numerical Pain Rating Scale score was 1.6 at final follow-up. - Conclusion - Our long-term study showed acceptable survival and functional results using the GRR in older patients, while young patients had less favorable survival.